2014
DOI: 10.1111/jop.12287
|View full text |Cite
|
Sign up to set email alerts
|

Cryogun cryotherapy for oral leukoplakia and adjacent melanosis lesions

Abstract: Cryogun cryotherapy is an effective treatment modality for OLM lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…They report advantages such as bloodless surgery, a low chance of secondary infection, and a relative lack of scarring and pain . A recent study by Chen et al using a ‘cryogun’ for 72 oral leukoplakia lesions, which included 26 mild dysplasia, 7 moderate dysplasia, and 1 severe dysplasia, showed complete regression after multiple cryotherapy sessions. At a mean follow‐up time of 18 months, 8 lesions had recurrences but were effectively controlled by repeated treatment.…”
Section: Conservative Management (Active Surveillance/wait‐and‐see Pomentioning
confidence: 99%
“…They report advantages such as bloodless surgery, a low chance of secondary infection, and a relative lack of scarring and pain . A recent study by Chen et al using a ‘cryogun’ for 72 oral leukoplakia lesions, which included 26 mild dysplasia, 7 moderate dysplasia, and 1 severe dysplasia, showed complete regression after multiple cryotherapy sessions. At a mean follow‐up time of 18 months, 8 lesions had recurrences but were effectively controlled by repeated treatment.…”
Section: Conservative Management (Active Surveillance/wait‐and‐see Pomentioning
confidence: 99%
“…Cryotherapy: Weakly recommended. A meta-analysis (n = 330) of 5 studies aimed at cryotherapy for OLK [33][34][35][36][37] found that after cryotherapy, the total recurrence rate was 16% (95% CI, 10%-25%) during an average follow-up period of 23 months. Among them, 3 studies reported the follow-up time and malignant transformation rate.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 3 studies reported the follow-up time and malignant transformation rate. Two studies 34,36 with a mean follow-up of 22 months (7-38 months) and 18 months (3-41 months), respectively, did not report the malignant transformation rate, and a study 35 with an average follow-up of 52.8 months (2-127 months) reported a malignant transformation rate of 5.4%.…”
Section: Resultsmentioning
confidence: 99%
“…OLM lesions in patients without smoking habit, with the greatest diameter < 2.8 cm, with epithelial dysplasia, or with a surface keratin thickness 50 mm needed significantly fewer cryogun cryotherapy treatments to achieve complete regression of the OLM lesions than the corresponding OLM lesions. 4 Therefore, we suggest that cryogun cryotherapy is also an effective treatment modality for OLM lesions.…”
mentioning
confidence: 99%